Street Vendors Hypergrowth: Consequence of Uncontrolled Urbanization In Semarang City - Sariffuddin, Sariffuddin; Wahyono, Hadi; Brotosunaryo, Brotosunaryo (Universitas Negeri Semarang, 2017)
This paper aims to understand the role of urbanization in the emergence of in urban area street vendors. In the case of Semarang, more than 54% of its street vendors come from its hinterlands. These sectors turn to development dichotomy that have a positive and negative impact. Positively, this area becomes people’s economic resilience. In the negative side, more than 60% of vendors make their stall in the public space. This research uses a mix-method approach taking 271 samples, Focus Group Discussion (FGD) and in-depth interview. From this study, it can be concluded that urbanization has led to the outbreak of street vendors through (1) rural-urban migration, and (2) social change as a result of gentrification. Working as street vendors turned out to be an alternative way of life to adapt to global economic uncertainty. Also, there are 71.6% of street vendors open their stalls in 2003-2009, or about 6-7 years after the monetary crisis (1997). It shows that the financial crisis is not the primary trigger for the outbreak of street vendors. Another interesting finding is that there is a new phenomenon in the form of the intervention of the middle class who took part in this business.